International law on peacekeeping : a study of Article 40 of the UN charter - Nasu, Hitoshi (Martinus Nijhoff Publishers, 2009)
While the upsurge of incidents in which the UN Security Council has been invoking Chapter VII: Action with Respect to Threats to the Peace, Breaches of the Peace, and Acts of Aggression has been seen as a sign of renewed authority for the Security Council, others have suggested that it is more a symptom of failure to prevent conflict in the first place. One of the latter, Nasu (law, Australian National U. College of Law, Australia) suggests that a renewed attention to Chapter VII's Article 40--allowing the Security Council to call for provisional measures to be undertaken by the conflicting pa.